Solitary internal jugular vein invasion by thyroid carcinoma: resection and reconstruction. - Fotis, Theofanis; Konstantinou, Evangelos; Mariolis-Sapsakos, Theodoros; Mitsos, Aristotelis; Restos, Stylianos; Katsenis, Konstantinos; Elefsiniotis, Ioannis; Kapellakis, George (J Vasc Nurs, 2009)
Thyroid carcinoma usually presents as asymptomatic thyroid nodule. Thyroid cancer may show microscopic vascular invasion; however, internal jugular vein (IJV) invasion is a rare complication of thyroid cancer. We present a case of unilateral invasion of IJV caused by local nodal recurrence of the primary thyroid carcinoma. The patient had undergone a near total thyroidectomy, followed by modified left lymph node resection with left IJV resection. In this case, the infiltrated part of the right IJV was resected, and the vessel was reconstructed using saphenous vein autograft. In locally advanced, well-differentiated thyroid cancers, only the radical resection relieves symptoms and increases survival.
Keywords: Biopsy, Fine-Needle; Carcinoma, Papillary; Female; Humans; Jugular Veins; Lymph Node Excision; Lymphatic Metastasis; Middle Aged; Neck Dissection; Neoplasm Invasiveness; Neoplasm Recurrence, Local; Palliative Care; Patient Selection; Radiotherapy, Adjuvant; Rare Diseases; Saphenous Vein; Thyroid Neoplasms; Thyroidectomy; Vascular Neoplasms